Electronica, gender and French cinematic girlhood in Céline Sciamma's films. Issue 3 (1st October 2020) - Edney, Gemma
ABSTRACT: This article examines the music in Céline Sciamma's films with an emphasis on Naissance des pieuvres (2007), arguing that, in a film where the girl characters so rarely express themselves through dialogue, the music offers a means of communication that does not rely on the verbal. It is through music that this film invites the spectator into the girls' cinematic world, and this music provides an insight into the sensations and emotions that the girls experience. The article argues that the use of the electronic genre increases this potential for expression. Because electronic music is bound up in French musical culture, and because it offers specific opportunities for female expression, the genre is particularly significant in a French girlhood film. This article examines how the electronic genre aids in the creation of a specifically 'girl' space in Céline Sciamma's films offering the girls a space in which they can express themselves freely without pre-existing signification or stereotypes. Via both the musical sounds themselves and the signification attached to the electronic genre, the film's music provides an audible expression of the characters' experiences, inviting us into the girls' cinematic space and allowing us a point of entry into their world.